Integrated transcriptomic and metabolomic analysis provides insight into the pollen development of CMS-D1 rice - Wang, Jie; Ying, Suping; Long, Weixiong; Luo, Lihua; Qian, Mingjuan; Chen, Wei; Luo, Laiyang; Xu, Weibiao; Li, Yonghui; Cai, Yaohui; Peng, Xiaojue; Xie, Hongwei (BMC plant biology, 2024)
Cytoplasmic male sterility (CMS) has greatly improved the utilization of heterosis in crops due to the absence of functional male gametophyte. The newly developed sporophytic D1 type CMS (CMS-D1) rice exhibits unique characteristics compared to the well-known sporophytic CMS-WA line, making it a valuable resource for rice breeding. In this research, a novel CMS-D1 line named Xingye A (XYA) was established, characterized by small, transparent, and shriveled anthers. Histological and terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL) assays conducted on anthers from XYA and its maintainer line XYB revealed that male sterility in XYA is a result of delayed degradation of tapetal cells and abnormal programmed cell death (PCD) of microspores. Transcriptome analysis of young panicles revealed that differentially expressed genes (DEGs) in XYA, compared to XYB, were significantly enriched in processes related to chromatin structure and nucleosomes during the microspore mother cell (MMC) stage. Conversely, processes associated with sporopollenin biosynthesis, pollen exine formation, chitinase activity, and pollen wall assembly were enriched during the meiosis stage. Metabolome analysis identified 176 specific differentially accumulated metabolites (DAMs) during the meiosis stage, enriched in pathways such as α-linoleic acid metabolism, flavone and flavonol biosynthesis, and linolenic acid metabolism. Integration of transcriptomic and metabolomic data underscored the jasmonic acid (JA) biosynthesis pathway was significant enriched in XYA during the meiosis stage compared to XYB. Furthermore, levels of JA, MeJA, OPC4, OPDA, and JA-Ile were all higher in XYA than in XYB at the meiosis stage. These findings emphasize the involvement of the JA biosynthetic pathway in pollen development in the CMS-D1 line, providing a foundation for further exploration of the molecular mechanisms involved in CMS-D1 sterility.